Conceptual model of robust management of inertial open innovations in the context of digital transformation of the national innovation system - Zhukov Aleksandr; Pronichkin Sergey; Kartsan Igor; Ovsianikova Natalia; Mihaylov Yuri (E3S Web of Conferences)
Dynamic development of network interaction between the subjects of the national innovation system as a mechanism for more intensive development of investment activity in the mining and metallurgical industry will be possible only with the introduction of a reliable system of management of open innovations. The complexity of reliable management is due, in particular, to the significant inertia of scientific and technical projects and works in various conditions associated, in particular, with changes in the intensity of scientific information flows. On the basis of system analysis of the problems of management of inertial open innovations in the mining and metallurgical industry, the feasibility of using regulatory structures with an internal model based on various feedback systems is proved. The regulator for robust control, tuned to the worst inertial mode of operation of existing structures, guarantees stability and leads to performance indicators that are not inferior to those set in other modes of operation.